A study to assess the effectiveness of demonstration on knowledge and practice regarding oxygen therapy among first-year nursing students in a selected nursing college - Dr. Ravindra H N; Ms. Zeba Khalifa; Ms. Jahnvi Prajapati; Ms. Khushali Patel; Mr. Jayrajsinh Parmar (The Bioscan, 2025)
Background: Oxygen therapy is a critical nursing procedure that requires comprehensive theoretical knowledge and precise practical skills. First-year nursing students often lack adequate exposure and competence in performing this procedure, which can impact patient safety and care quality. Aim: This study aimed to assess the effectiveness of demonstration as a teaching method in enhancing the knowledge and practice of oxygen therapy among first-year nursing students. Methods: A quasi-experimental one-group pre-test and post-test design was conducted among 300 first-year B.Sc. Nursing and GNM students in a selected nursing college. Participants were selected using purposive sampling. Data collection tools included a structured knowledge questionnaire and an observational checklist. A structured demonstration was conducted, followed by post-intervention assessments. Results: The study revealed a significant improvement in both knowledge and practice scores after the demonstration. The mean knowledge score increased from 14.12 ± 4.85 to 22.45 ± 3.60 (p < 0.001), and the mean practice score improved from 13.90 ± 1.85 to 15.25 ± 1.20 (p < 0.001). Chi-square analysis showed a significant association between pre-test knowledge scores and selected demographic variables like age, religion, and prior exposure to oxygen therapy. Conclusion: Demonstration-based teaching is an effective instructional strategy that significantly enhances the cognitive and psychomotor skills of nursing students in administering oxygen therapy. Incorporating such interactive and skill-focused methods into the nursing curriculum can bridge educational gaps and improve clinical competency. KEYWORDS: Oxygen Therapy, Nursing Education, Demonstration, Knowledge, Practice, Skill Acquisition